Cooperation in a Fragmented Society: Experimental Evidence on Syrian Refugees and Natives in Lebanon - Michalis Drouvelis; Bilal Malaeb; Michael Vlassopoulos; Jackline Wahba (Institute of Labor Economics (IZA), 2019)
Lebanon is the country with the highest density of refugees in the world, raising the question of whether the host and refugee populations can cooperate harmoniously. We conduct a lab-in-the-field experiment in Lebanon studying intra- and inter-group behavior of Syrian refugees and Lebanese nationals in a repeated public good game without and with punishment. We find that homogeneous groups, on average, contribute and punish significantly more than mixed groups. These patterns are driven by the Lebanese participants. Our findings suggest that it is equally important to provide adequate help to the host communities to alleviate any economic and social pressures.
Keywords: D91; J5; F22; 330; refugees; public good game; cooperation; punishment